Pengaruh Kepatuhan Berhijab Terhadap Perilaku Keagamaan Siswi di SMA Al Falah Cibinong Bogor - Hilda Nurahmah; Alek Maulana; Nana Mulyana (Advances In Education Journal, 2026)
This research aims to analyze the influence of hijab adherence on the religious     behavior of female students at SMA Al Falah Cibinong Bogor. The     phenomenon underlying this research is the importance of examining whether     the obligation to wear the hijab at school has been internalized as a spiritual     value or is merely a formality of adhering to school regulations. The method     used in this research is correlational quantitative with 94 female students as     respondents, utilizing a questionnaire as the main instrument and statistical     analysis techniques to test the validity and reliability of the data. Data on hijab     adherence  is  measured  thru  indicators of  understanding,  consistency,     compliance with rules, and internal motivation in its practice. Meanwhile,     religious behavior is measured thru indicators of worship practices, personal     morals, social morals, obedience, norms, religious commitment, enthusiasm for     religious knowledge, respect for religious symbols, and interaction with the     Qur'an. The results of this study indicate that the level of hijab adherence and     religious behavior among the female students falls into a high category. Data     analysis proves the existence of a positive and significant influence between     hijab adherence and religious behavior. This indicates that the higher the level     of adherence among female students in wearing the hijab, the better their     religious behavior will be, which will be reflected in their daily lives. This result     serves as a foundation for the school to continue strengthening spiritual guidance so that wearing the hijab becomes a personal awareness for the students, not just a rule in the code of conduct.